Evaluating the effectiveness of basel iii implementation in credit risk management at Sai Gon Thuong Tin commercial joint stock bank (SACOMBANK) - Pham Le, Minh Tu (Technium Business and Management, 2026)
In the context that Saigon Thuong Tin Commercial Joint Stock Bank (Sacombank) is gradually completing its ten-year restructuring plan and moving towards risk standardization under Basel III, this study aims to assess the impact of Basel III standards on credit risk management at Sacombank from 2013 to 2024. The research analyzes the theoretical framework of credit risk and the principles of Basel III. The author uses the ARDL regression method to measure the impact of key Basel III factors such as capital adequacy ratio (CAR), profitability ratio (ROAA) and macroeconomic factors on the non-performing loan ratio (NPL) at Sacombank. The findings indicate that Sacombank has made significant progress in controlling credit risk under Basel III. Both CAR and ROAA have a substantial impact on NPLs. The study goes beyond univariate analysis by clarifying the interrelationships among the factors and their influence on credit risk. This study proposes a set of solutions enabling Sacombank to flexibly implement Basel III, thereby enhancing its risk response capacity and promoting the standardization of credit operations in line with international best practices.